An Interrogation of the types of Grammatical Cohesive Devices that are Prominent in the Writing of Hearing-Impaired Learners - Somba Mang’oka James Onyango Ogola Phylis Bartoo, Antony (2019)
This paper set out to interrogate the types of grammatical cohesive de vices that learners with hearing-impaired use in their writing. Studie s conducted on the subject reveal that hearing-impaired learners face several challenges in their written English. To try to aid in providin g solutions for amicable communication in the written works of these l earners with hearing problems, this article investigated the nature of cohesion in the hearing-impaired learners’ English written texts. It investigated ways by which hearing-impaired learners have been able to achieve cohesion in their written texts. To be able to interrogate th e cohesion devices, the article located itself within the lens of Hall iday and Hasan’s theory of Cohesion to identify, describe and categori se cohesive devices in the texts. In the final analysis, the paper fou nd out that all the cohesive devices posited by Halliday and Hasan wer e present, but at varying frequency. Reference had the highest frequen cy of occurrence and ellipsis the least. The findings of this study pr ovide a theory-governed description of cohesive ties used by the heari ng-impaired learners in Kenya. The findings also contribute to the inc reasing body of knowledge in studies related to the writing and commun ication of deaf learners.